2012
DOI: 10.1007/s00296-012-2543-9
|View full text |Cite|
|
Sign up to set email alerts
|

Dual downregulation of microRNA 17-5p and E2F1 transcriptional factor in pediatric systemic lupus erythematosus patients

Abstract: The main objective of this study is to investigate the relative expression of miRNA 17-5p and one of its target genes E2F1 in the peripheral blood of systemic lupus erythematosus pediatric patients. The expression of miRNA 17-5p and its target E2F1 mRNA was analyzed by TaqMan real-time qPCR. Our results showed significant downregulation of miRNA 17-5p in SLE patients compared to healthy controls; moreover, miRNA 17-5p was more downregulated in patients on no treatment compared to those on treatment. Relative e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…Several inflammasome-regulating miRNAs are downregulated in SLE: miR-223-3p in naive B cells of SLE patients (112), miR-20a-5p in monocytes (113), and miR-17-5p in PBMCs of adult (114) and pediatric SLE patients (115). Moreover, miR-17-5p levels are diminished in untreated patients compared with those on treatment (116). Regarding lupus nephritis, Several transcripts coding for proteins that act as regulators of the NLRP3 inflammasome are targeted by miRNAs.…”
Section: Inflammasome-regulating Mirnas In Human Autoimmune Diseasesmentioning
confidence: 99%
“…Several inflammasome-regulating miRNAs are downregulated in SLE: miR-223-3p in naive B cells of SLE patients (112), miR-20a-5p in monocytes (113), and miR-17-5p in PBMCs of adult (114) and pediatric SLE patients (115). Moreover, miR-17-5p levels are diminished in untreated patients compared with those on treatment (116). Regarding lupus nephritis, Several transcripts coding for proteins that act as regulators of the NLRP3 inflammasome are targeted by miRNAs.…”
Section: Inflammasome-regulating Mirnas In Human Autoimmune Diseasesmentioning
confidence: 99%
“…This signaling cascade is associated with a number of cell functions, including cell development, differentiation and apoptosis (Table ). However, a number of studies identified a role for miR‐17‐5p in several cancers (Chen et al, ; Hufbauer et al, ), immune response, Philadelphia chromosome‐negative myeloproliferative neoplasm (Hussein, Dralle, Theophile, Kreipe, & Bock, ), pediatric systemic lupus erythematosus (Aboelenein, Salah, Lashine, & Abdelaziz, ) and progression of lipid metabolism (Fontana et al, ; Klöting et al, ). However, a relationship between miR‐17‐5p and neurodegeneration is yet to be reported.…”
Section: Discussionmentioning
confidence: 99%
“…However, a relationship between miR‐17‐5p and neurodegeneration is yet to be reported. The transcription factor E2F1, a direct downstream target of c ‐myc, is negatively regulated by miR‐17‐5p, which may partially account for the antiapoptotic effects of these miRNAs (Aboelenein et al, ). Taken together, we speculate that the aberrant expression of miR‐17‐5p might partly be involved in PQ‐induced neurotoxicity, contributing to antiapoptotic effects and may play a critical role in the pathology of PD.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation